Enantioselective behaviour of tetraconazole during strawberry wine‐making process. Issue 5 (12th March 2018) - Liu, Na; Pan, Xinglu; Zhang, Shuang; Ji, Mingshan; Zhang, Zhihong
Abstract: The fate of tetraconazole enantiomers in strawberries during wine‐making process was studied. The residues were determined by ultra‐performance convergence chromatography tandem triple quadrupole mass spectrometry after each process steps. Results indicated that there was significant enantioselective dissipation of tetraconazole enantiomers during the fermentation process. And (−)‐tetraconazole degraded faster than (+)‐tetraconazole. The half‐lives of (−)‐tetraconazole and (+)‐tetraconazole were 3.12, 3.76 days with washing procedure and 3.18, 4.05 days without washing procedure. The processing factors of strawberry wine samples after each step were generally less than 1. In particular, the processing factors of the fermentation process were the lowest. The results could help facilitate more accurate risk assessments of tetraconazole during wine‐making process. Abstract :